Correlation between changes in serum levels of GDF11 and Cdc42 and major adverse cardiovascular events in maintenance hemodialysis elders - Qiang Lei; Qi-meng Xia; Chun-rong Du (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the changes in serum levels of growth differentiation factor 11 （GDF11） and cell division cycle 42 （Cdc42） in maintenance hemodialysis （MHD） elders and examine their correlations with events and occurrence of major adverse cardiovascular events （MACE）. Methods From June 2019 to June 2021, 164 MHD elders were selected as observation subjects （hemodialysis group） while 150 ESRD elders undergoing no hemodialysis during the same period as non-hemodialysis group. And 148 healthy elders receiving physical examinations were designated as control group. According to whether or not MACE occurred within 2 years, they were assigned into two groups of non-MACE （n = 92） and MACE （n = 72）. Enzyme-linked immunosorbent assay （ELISA） was utilized for determining serum levels of GDF11 and Cdc42. Multivariate Logistic regression was applied for examining the influencing factors of 2-year MACE and receiver operating characteristic （ROC） curve for determining the predictive value of GDF11 and Cdc42 levels for MACE. Results As compared with control, non-hemodialysis and hemodialysis groups, serum level of GDF11 [（640.38 ± 137.55）vs（851.56 ± 215.61），（785.27 ± 174.62）μg/L]declined obviously in hemodialysis group （t = 10.414, P＜0.001） while Cdc42 level rose sharply [（57.22 ± 11.34） vs （35.61 ± 10.25）, （43.58 ± 10.72） μg/L] （t = 17.589, P＜0.001）. Cdc42 levels [（65.31 ± 21.22） vs （50.89 ± 15.56） μg/L] were obviously higher in MACE group than those in non-MACE group. GDF11 level [（576.56 ± 125.71） vs （690.33 ± 159.84） μg/L] was obviously lower than that in non-MACE group and the differences were statistically significant （P＜0.05）. AUC of GDF11/Cdc42 level and their combined prediction for MACE was 0.762, 0.794 and 0.868 respectively. The value of combined prediction was better than that of individual prediction （Z = 3.183, 3.047; P = 0.002, 0.002）. Conclusion In MHD elders, lower serum level of GDF11 and higher level of Cdc42 are correlated closely with the occurrence of MACE. GDF11 and Cdc42 may be used as markers for managing and assessing ESRD MHD elders.